Analisis Faktor-Faktor Akuntabilitas Pengelolaan Dana Desa - Warih Ning Sabdosih; Aris Edy Sarwono (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
The purpose of this study to describe the factors that influence the accountability of managing village funds in Nawangan District, Pacitan Regency. In this study using qualitative methods, the data used are secondary data obtained from reference sources that have a relationship with the research objectives. The results of this study indicate that community participation, competence of village officials, use of information technology and internal control systems affect the accountability of managing village funds.